2022
DOI: 10.1097/jmq.0000000000000036
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of an Electronic Health Record Integrated Clinical Pathway Improves Adherence to COVID-19 Hospital Care Guidelines

Abstract: Background: During the COVID-19 pandemic, frequently changing guidelines presented challenges to emergency department (ED) clinicians. The authors implemented an electronic health record (EHR)-integrated clinical pathway that could be accessed by clinicians within existing workflows when caring for patients under investigation (PUI) for COVID-19. The objective was to examine the association between clinical pathway utilization and adherence to institutional best practice treatment recommendations … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“…3,4 Automation of modern health care systems covers many fields and necessitates the computerization of hospital processes to streamline health care services, reduce paperwork, collect digital data for data analytics, and control costs 5,6 . The CP was not an exception in this regard, as many studies reported the development of computerized CPs [7][8][9][10][11][12][13][14][15][16] . By analyzing the literature, we found that the common theme in most studies is that the computerization process was directed mainly toward either connecting CPs with Electronic Medical Record (EMR) systems or computerizing CPs without standardizing their contents.…”
Section: Introductionmentioning
confidence: 99%
“…3,4 Automation of modern health care systems covers many fields and necessitates the computerization of hospital processes to streamline health care services, reduce paperwork, collect digital data for data analytics, and control costs 5,6 . The CP was not an exception in this regard, as many studies reported the development of computerized CPs [7][8][9][10][11][12][13][14][15][16] . By analyzing the literature, we found that the common theme in most studies is that the computerization process was directed mainly toward either connecting CPs with Electronic Medical Record (EMR) systems or computerizing CPs without standardizing their contents.…”
Section: Introductionmentioning
confidence: 99%